5d-6=36

Simple and best practice solution for 5d-6=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5d-6=36 equation:


Simplifying
5d + -6 = 36

Reorder the terms:
-6 + 5d = 36

Solving
-6 + 5d = 36

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 5d = 36 + 6

Combine like terms: -6 + 6 = 0
0 + 5d = 36 + 6
5d = 36 + 6

Combine like terms: 36 + 6 = 42
5d = 42

Divide each side by '5'.
d = 8.4

Simplifying
d = 8.4

See similar equations:

| 5x+9+2x-4= | | 48*5.5%*0.075/170-2*0.015= | | 11x-2y=-22 | | (4x-7)-(-10x+6)= | | 0.362y=3.20001x+63 | | 6-w=-40 | | K-2+7-9k= | | l+17=90 | | X^2-15=-8x | | 7x+5y=190 | | 7p+2=6+6p | | 48*5.5%*0.075/170*0.015= | | -.75(8x-12)-9=-2x | | (5k-10)-0-9= | | (4x+3)(3x-4)=0 | | yb+ax=c | | Y-2=(-2-3) | | 1.32(x+y)=32 | | Y-2=(-3-3) | | 12=6x-8x | | 284.7+14.6= | | -14.4=-0.6 | | 3(x*31)=31.3 | | 3s-6=5 | | -7k-9=1 | | 3x+-8y+4=11 | | 7x+4=-6x-22 | | 6(d+7)-20=6x | | 0.66+4=-0.33x-4 | | 3(10)=2y+6 | | 24+8k=9 | | 3(8)=2y+6 |

Equations solver categories